Cephalometrics for Orthognathic Surgery: Insights from Literature Review - Vikram Karande; Neelam Andrade; Vaishali Pagare; Sejal Bhaskar; Ritik Kashwani (The Bioscan, 2025)
This literature review examines the role of cephalometric evaluation in orthognathic surgery, highlighting its significance in diagnosis, treatment planning, and postoperative assessment. By analyzing various studies, the review highlights key cephalometric parameters and their applications in predicting surgical outcomes, improving facial aesthetics, and ensuring functional balance. The findings underscore the value of cephalometric analysis as a critical tool for enhancing surgical precision and patient-specific treatment approaches in orthognathic procedures.